All-women theatre in Saudi Arabia. (1st December 2021) - Al-Aqeel, Ohood
The subject matter of women's creative experience and contribution to the theatre in Saudi Arabia is challenging, as it relates to the reality of Saudi society. Women were not entitled to participate in the theatre based on the cultural and social values of Saudi society: during the emergence of modern arts in the country, its conservative society refused to allow women's appearance on stage. The social ban resulted in an institutional ban, which made many male playwrights take the female component out of their texts. There is no doubt that, to an extent, this resulted in the delay of women's direct involvement in the Saudi Arabian theatre and is what prompted women to take an interest in finding a theatre that suited their needs. This article investigates the appearance of the so-called all-women theatre, its successes and shortcomings, and presents an argument about the role of official and commercial venues in assisting this unique theatrical experience. It also applies a critical analysis to two plays by Wafaa Al-Tayeb, who wrote mainly for the all-women theatre: After Me, The Deluge and With a Pink Ribbon, both published in a collection in 2016. It is hoped that this article can trace most of the cultural, social and commercial aspects that shaped these plays and gave them their characteristics.